Pengaruh pasang surut air laut terhadap kekuatan beton komposit material Ground Granulated Blast Furnace Slag (GGBFS) - Muhammad Kemal Rafif; Alfinna Mahya Ummati (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2023)
Concrete is a material that is commonly used to build infrastructure in various environmental conditions, but concrete has a weakness in environments exposed to salt water. So, the engineer intends to research the impact of exposure to sea water on the compressive strength and split tensile strength of concrete, and use GGBFS as a substitute for cement to reduce the impact of exposure to sea water on concrete. In this study, researchers will conduct experiments by exposing concrete to artificial seawater with dry-wet cycles with immersion durations of 24 hours, 16 hours, and 8 hours, as an interpretation of the tide cycle. The test results obtained are by adding 20% of GGBFS to the concrete mixture, the concrete will experience an increase in performance from 29.06 MPa on compressive strenght and 2.34 MPa on tensile split strenght to be 32.17 MPa on compresive dan 2.64 on tensile split strenght compared to concrete without the addition of GGBFS, and by exposing it to seawater for 24 hours, concrete with 20% GGBFS mixture has compressive strength which is better than normal concrete without GGBFS mixture, but with 40% GGBFS content the concrete will decreases in performance to 26.98 MPa. Meanwhile, based on the immersion method using sea water that has been carried out, the decrease in concrete performance is most significant to 24.15 MPa in compressive streght when it experiences an 8-hour soaking cycle. This proves that concrete exposed to sea water will experience a decrease in strength, especially in extreme tidal conditions. Utilization of GGBFS as a concrete mix is an effort to utilize waste, but there are ideal proportions and mixing techniques that need to be considered, so that waste concrete does not experience a significant loss of performance.